Antibiofilm effect of C-10 massoia lactone toward polymicrobial oral biofilms - Diyah Tri Utami; Sylvia Utami Tunjung Pratiwi; Herman P Spaink; Tetiana Haniastuti; Triana Hertiani (Wolters Kluwer Medknow Publications, 2021)
This study is aimed to test the efficacy of C-10 Massoia lactone in oral polymicrobial degradation. Polymicrobial of Streptococcus sanguinis, Streptococcus mutans, Lactobacillus acidophilus, and Actinomyces viscosus were studied. C-10 Massoia lactone against biofilm degradation was investigated using modified crystal violet for biofilm staining. The effectiveness of C-10 Massoia lactone against biofilms was calculated by the minimum biofilm inhibitory concentration (MBIC50) and the minimum value of biofilm eradication concentration (MBEC50). Scanning electron microscope was used to study biofilm cell viability and morphological changes. The results showed a degradation effect of C-10 Massoia lactone against mature oral polymicrobial at 0.25% v/v. C-10 Massoia lactone can degrade polymicrobial biofilms of S. mutans, S. sanguinis, L. acidophilus and A. viscosus. This compound can destroy the extracellular polymeric substances (EPS) of polymicrobial biofilms. The potential application of C-10 Massoia lactone for anti-polymicrobial medication should be applied in such a way that any negative effects are minimized. Further research is needed to confirm the findings of this study.